Inter-organisational communication: organisational future orientation, interorganisational interaction quality and interorganisational group mechanism - Mutebi, Henry; Muhwezi, Mose; Ntayi, Joseph M.; Munene, John C. (Journal of International Humanitarian Action, 2022)
The purpose of this study is to investigate the effect of organisational future orientation and interaction quality on inter-organisational communication, and the mediating role of inter-organisational group mechanism on the relationship between organisational future orientation, interaction quality and inter-organisational communication. A questionnaire assessing the experience of organisational future orientation, inter-organisational interaction quality, inter-organisational group mechanism and inter-organisational communication was administered to 101 out of 136 humanitarian organisations delivering social services to refugee settlements in Uganda. The proposed hypotheses were tested using PLS-SEM in the SmartPLS version 3.3.0 for professionals. The paper found that organisational future orientation has a positive impact on inter-organisational communication. Inter-organisational group mechanism partially mediates organisational future orientation and inter-organisational communication whilst it fully mediates the relationship between inter-organisational interaction quality and inter-organisational communication. The findings of this research provide useful insights into the role of inter-organisational group mechanism in boosting the role of organisational future orientation and interaction quality in inter-organisational communication in humanitarian relief delivery. Hence, a high level of inter-organisational group mechanism not only improves inter-organisational communication in humanitarian relief delivery but also enhances the benefits of organisational future orientation and interaction quality for inter-organisational communication. This research is one of the limited studies that investigate the effect of organisation future orientation and interaction quality on inter-organisational group mechanism and inter-organisational communication in humanitarian relief delivery in sub-Saharan Africa.
Keywords: Inter-organisational communication; Organisational future orientation; Interorganisational interaction quality; Interorganisational group mechanism